Time trends and regional differences in maternal mortality in China from 2000 to 2005 - Gao Yanqiu; Carine Ronsmans; An Lin (The World Health Organization, 2009)
OBJECTIVE: To examine trends and variations in maternal mortality in China between 2000 and 2005. METHODS: We used Poisson regression analysis of data from the Chinese National Maternal and Child Health Routine Reporting System between 2000 and 2005 to identify time trends in the maternal mortality ratio (MMR) by province and region. FINDINGS: The MMR declined by an average of 5% per year (crude relative risk, RR: 0.95; 95% confidence interval, CI: 0.94-0.97). There was no interaction between region and year (P = 0.2311). Mortality declined by 5% per year in the eastern region (crude RR: 0.95; 95% CI: 0.92-0.97), by 5% per year in the central region (crude RR; 0.95; 95% CI: 0.94-0.96), and by 4% per year in the western region (crude RR: 0.96; 95% CI: 0.94-0.98). The absolute difference in MMR between the western and eastern regions declined from 65.4 deaths per 100 000 live births in 2000 to 49.4 per 100 000 live births in 2005. CONCLUSION: China is making good progress towards achieving the fifth Millennium Development Goal, and there is no evidence of a widening gap between better-off and economically more deprived provinces.